2010
DOI: 10.1007/s10295-010-0804-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of l-lactic acid by Rhizopus oryzae using semicontinuous fermentation in bioreactor

Abstract: Semicontinuous fermentation using pellets of Rhizopus oryzae has been recognized as a promising technology for L-lactic acid production. In this work, semicontinuous fermentation of R. oryzae AS 3.819 for L-lactic acid production has been developed with high L-lactic acid yield and volumetric productivity. The effects of factors such as inoculations, CaCO₃ addition time, and temperature on L-lactic acid yield and R. oryzae morphology were researched in detail. The results showed that optimal fermentation condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 15 publications
1
12
0
5
Order By: Relevance
“…At the other CaCO 3 concentrations (0, 10, and 30 g/L), determined pHs were 4.4, 5.1, and 6.0, respectively. Optimal CaCO 3 concentration of 20 g/L was lower than those reported in the previous studies [25][26][27]. For example, Wu et al [27] reported that the maximum lactic acid production by R. oryzae was achieved when 50 g/L CaCO 3 were used as neutralizing agent.…”
Section: Effect Of Calcium Carbonate On L-lactic Acid Synthesis and Cmentioning
confidence: 85%
“…At the other CaCO 3 concentrations (0, 10, and 30 g/L), determined pHs were 4.4, 5.1, and 6.0, respectively. Optimal CaCO 3 concentration of 20 g/L was lower than those reported in the previous studies [25][26][27]. For example, Wu et al [27] reported that the maximum lactic acid production by R. oryzae was achieved when 50 g/L CaCO 3 were used as neutralizing agent.…”
Section: Effect Of Calcium Carbonate On L-lactic Acid Synthesis and Cmentioning
confidence: 85%
“…Glucose, however, has been reported to yield up to 0.90 g/g L-lactic acid (Wu et al, 2011), which also surpasses the yield and productivity, using xylose as substrate. Some improvements have nevertheless been made towards xylose conversion into L-lactic acid.…”
Section: Lactic Acidmentioning
confidence: 95%
“…In the cell growth stage, the zygomycetes are kept in a relatively rich medium. In the production stage, the produced biomass is cultivated in a nitrogen-limited medium to promote production of organic acids (Wu et al, 2011). Additional requirements for the organic acid production are oxygen-rich conditions and a neutralizing agent to maintain the pH-value in the medium (Zhang et al, 2007).…”
Section: Metabolites Of Zygomycetesmentioning
confidence: 99%
“…Rhizopus species, such as R. oryzae and R. arrhizus, have amylolytic enzymatic activity, which enables them to convert starch directly to L(+)-lactic acid. Several studies have reported on the use of Rhizopus for lactic acid production (Yin et al 1998;Liu et al 2006;Yu et al 2007;Guo et al 2010;Wu et al 2011;Saito et al 2012). Fig.…”
Section: Bioresourcescommentioning
confidence: 99%